Synthesis, physico-chemical characterization, and stability constants of metal complexes of pyridine-2-carbaldehyde thiosemicarbazone - Balaban, A; Sekerci, M; Erk, B (Marcel Dekker Inc, 2003)
The synthesis, physico-chemical properties and complexes with transition element cations of pyridine-2-carbaldehyde thiosemicarbazone (L) are reported. The synthesis and structural analysis of L, its complexes with MCl2 (M = Mn(II), Zn(II), Cd(II)) and (MCl3)-Cl-1 (M-1 = Cr(III), Co(III)) salts are reported. Their general formulas are [M(L)(3)]Cl-3.3H(2)O [M = Cr(III) and Co(III)], [M(L)(H2O)Cl]Cl [M = Zn(II) and Mn(II)] and [Cd(L)Cl-2)]-H2O-Mn(II), Zn(II), Cd(II) complexes with a metal-ligand ratio 1:1 and Cr(III), Co(III) complexes with a metal-ligand ratio 1:3 have been prepared. Molecular structures of these complexes were identified using elemental analyses, FT-IR UV-Vis, thermogravimetric (TGA) and conductivity techniques. The structure, along with other physico-chemical studies, establishes that the complexes of L, except for the cobalt complex, are low-spin. Spectroscopic analysis shows that the transition metal complexes have octahedral or tetrahedral geometry. For the Cr(III) and Co(III) complexes octahedral geometry is proposed, and the Zn(II), Cd(II) and Mn(II) complexes are proposed to be of tetrahedral geometry. The stability constants of the Zr(II) and Mn(II) complexes were determined by the Job method. The stability constants of the Zn(II) and Mn(II) complexes were found to be 8.77 x 10(4) M-1 and 6.40 x 10(5) M-1, respectively. The increase in stability constants follows the order of Zn(II) > Mn(II) and this increase is in agreement with the Irving-Williams series.
Keywords: Schiff-Base Complexes; 1-Formylisoquinoline Thiosemicarbazone; Uo2(Vi) Complexes; Crystal-Structure; Ni(Ii); Cu(Ii); Co(Ii); 2-Acetylpyridine; Copper(Ii); Monohydrate